Direct and indirect patient costs of tuberculosis care in India. Issue 7 (12th May 2020) - Chandra, Ankit; Kumar, Rakesh; Kant, Shashi; Parthasarathy, Raghavan; Krishnan, Anand
Abstract: Objective: To synthesise the evidence for estimating the direct and indirect patient costs of drug‐sensitive and drug‐resistant tuberculosis care in India. Method: PubMed, Embase, Web of Science, IndMED and Google Scholar were searched for studies conducted in India between 2000 and 2018 and published in English. The search terms were "tuberculosis" AND "costs" (cost Analysis, economics, cost of illness, health care costs, health expenditures, direct service costs, catastrophic cost) AND "India". The cost of TB care was from the patient's perspective. Data regarding costs were extracted, indexed to the year 2018 using cumulative inflation rate and converted to US dollars at the exchange rate of 2018. Results: Thirteen studies were included in this review. The mean (unweighted) total cost incurred by patients being treated for drug‐sensitive TB in a public health facility was $ 235.00 (SD‐ 222.10), and the median of means was $ 170.60 (range – 43.70–718.40). The mean direct cost was 45.5% of the total cost. Only one study, which was conducted in a private facility, reported the mean total cost for drug‐resistant TB as $ 7778.04. Catastrophic cost (total cost ≥ 20% of the total annual household income) was experienced by 7% to 32.4% of drug‐sensitive TB patients and by 68% of drug‐resistant TB patients. Conclusion: Despite free diagnostic and treatment services provided under the Revised National Tuberculosis Control Programme, the patient cost of tuberculosis care is high. Relevant studies vary widely in methodology and cost reporting. Abstract : Objectif: Synthétiser les données probantes permettant d'estimer les coûts directs et indirects des soins anti‐TB pour les patients avec une TB sensible ou résistante aux médicaments en Inde. Méthode: PubMed, Embase, Web of Science, IndMED et Google Scholar ont été recherchés pour des études menées en Inde entre 2000 et 2018 et publiées en anglais. Les termes de recherche étaient 'tuberculose' ET 'coûts' (analyse des coûts, économie, coût de la maladie, coûts des soins de santé, dépenses de santé, coûts directs des services, coût catastrophique) ET 'Inde'. Le coût des soins anti‐TB était du point de vue du patient. Les données concernant les coûts ont été extraites, indexées pour l'année 2018 en utilisant le taux d'inflation cumulé et converties en dollars US au taux de change de 2018. Résultats: Treize études ont été incluses dans cette revue. Le coût total moyen (non pondéré) encouru par les patients traités pour une TB sensible aux médicaments dans un établissement de santé public était de 235, 00 USD (SD‐222, 10), et la médiane des moyennes était de 170, 60 USD (intervalle ‐ 43, 70 ‐ 718, 40). Le coût direct moyen était de 45, 5% du coût total. Une seule étude, qui a été menée dans un établissement privé, a rapporté le coût moyen total pour la TB résistante aux médicaments équivalent à 7.778, 04 USD. Des coûts catastrophiques (coût total ≥ 20% du revenu annuel total du ménage ) ont été subis par 7% à 32, 4% des patients avec une TB sensible aux médicaments et par 68% des patients avec une TB résistante aux médicaments. Conclusion: Malgré les services gratuits de diagnostic et de traitement fournis dans le cadre du Programme National Révisé de Lutte contre la TB, le coût des soins anti‐TB pour les patients est élevé. Les études pertinentes varient considérablement dans la méthodologie et la communication des coûts.